Misantropi e uomini del sottosuolo. Personaggi dalla narrativa italiana contemporanea (ENTHYMEMA, 2020)
In this contribution, I will analyze a specific variation of the modern and contemporary literary character – which I call “archetype of misanthrope” – in the field of contemporary Italian fiction. Within the broad gallery of modern fictional characters, it is possible to isolate some paradigmatic cases of the posture of the misanthrope. The most direct reference is Dostoevsky's “man of the underground” (1864). However, there is a wide gamut of texts in which a first-person narrator exhibits his condition of social and human isolation, and articulates a pessimistic or apocalyptic vision of the historical context – through the tones of political invective. This form of novel-monologue and this declination of the character are typical of the modernist narrative and of its persistence in the subsequent narrative. Specifically, my talk focuses on a specific trait which characterizes the “archetype of misanthrope”, which I find in the texts of Italian authors published between the 1990s and the 2000s.